SME investment report 2024: Developments between 2016 and 2023 - Kren, Janez; O’Regan, Cynthia; O'Toole, Conor; Rehill, Luke; Smith, Alice (ESRI, 2025)
Despite a robust domestic economic performance, over the past number of years, the Irish enterprise sector has been hit with a series of external shocks. From Brexit to the COVID-19 pandemic and then the external inflationary shocks following the energy price crisis, enterprises have faced challenges that have put pressure on their sustainability in day-to-day operations and heightened uncertainty around their commitment to capital investment. Yet long-term investment is critical to enhance productivity and drive profitability going forward. Over and above these external shocks, firms are grappling with the twin challenge of decarbonisation and digitalisation. Understanding the trends in investment is therefore critical to determining how firms are adapting to the changing circumstances and how Ireland’s economy is building capacity for future growth. Given this backdrop, this report provides a detailed examination of the SME investment across a range of asset categories. It explores how these investments are financed and the investment challenges faced by SMEs in the current environment. Although SMEs make up the bulk of firms and employment in Ireland, aggregate statistics on investment activity tend to be dominated by larger firms. This report uses firm-level data collected as a specific module on the Department of Finance Credit Demand Survey to provide a statistical review of the key trends in SME investment. The report presents data from the Credit Demand Survey conducted in 2024 for the investments in year 2023. Annual time series comparisons back to 2016, with the exception of 2022, are also provided for context and comparison. The main findings in each of the analytical chapters are provided below.